Pengaruh Beban Kerja dan Pengalaman Auditor Dalam Mendeteksi Kecurangan - Rahmawati Rahmawati; Halim Usman (Journal of Accounting and Investment, 2014)
The objective of research is to determine whether the workload and audit experience affect the auditor's ability to detect fraud. The data used in this study are primary data, samples are auditors of Inspectorate in Palopo City. Analysis of the data used is multiple linear regression analysis. Results indicate workloads does not has significant effect on the ability to detect fraud. Audit experience has effect on the ability to detect fraud.